Thermoforming sheet with protective film, decorative sheet, and molded article using same
Through the design of multi-layer thermoformed sheets, the pollution and deformation problems caused by the peeling of the protective film on the surface of the resin molded product are solved, and high yield chemical durability and scratch resistance are achieved. It is suitable for resin molded products in various fields.
Patent Information
- Application Number
- JP2021064629
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-04-06
- Publication Date
- 2025-02-12
- Estimated Expiration
- 2041-04-06
AI Technical Summary
When the prior art integrates design and function into the surface of resin molded articles, there is a problem of surface contamination and deformation caused by peeling of protective films, making it difficult to achieve high yield chemical durability and scratch resistance.
The thermoformed sheet with a multi-layer structure includes a polycarbonate resin layer, an acrylic resin layer and an uncured acrylate active ray curable resin layer. By controlling the glass transition temperature and interlayer differences, the stability and surface integrity of the protective film during the thermoforming process are ensured.
It achieves high yield chemical durability and scratch resistance, and is suitable for resin molded products in the fields of automotive interiors, electrical appliances, cosmetic boxes, building materials, etc., improving the surface appearance and processing performance.
Smart Images

Figure 0007628870000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a thermoforming sheet or decorative sheet with a protective film that is suitably used in a method of integrating a sheet imparted with a design or function with a resin molded article by thermoforming in order to impart chemical resistance, scratch resistance and design to the surface of the resin molded article with good yield, and to a molded article using the same. [Background technology]
[0002] In recent years, the number of plastic molded parts used in automobiles has been increasing due to the demand for diversifying automobile designs and reducing the weight of automobiles. These plastic molded parts are required to have designs such as wood grain or metallic tones, and functions such as chemical resistance and scratch resistance. As a method for imparting design and functionality, a method of integrating a sheet with a specific design or function, such as a decorative sheet, with a plastic molded product has been proposed. Specific examples include the following two methods: (1) a method in which a sheet is preformed into a specific shape by thermoforming (vacuum forming, compressed air forming, etc.), which is then set in an injection mold, and molten resin is injected into the molded product to form an injection molded product and simultaneously integrate it with the preformed sheet; and (2) a method in which a sheet is thermoformed to cover a prefabricated plastic molded product (three-dimensional surface decorative molding). Both of these methods (1) and (2) require the thermoforming of a sheet. The thermoforming sheet used has a hard coat layer to provide chemical resistance and scratch resistance, and the base sheet is required to be transparent so as not to interfere with the appearance of the design layer. For this reason, acrylic resins, polycarbonate resins, and polyester resins are generally used.
[0003] For example, Patent Document 1 discloses an example of a so-called two-stage curing method for a laminated hard-coated film in which an ultraviolet-curable hard-coat layer is formed on a substrate film in order to achieve a high degree of compatibility between surface robustness and formability. The hard-coat layer is cured with a weak ultraviolet exposure before three-dimensional molding, and then post-exposed after three-dimensional molding, thereby achieving both formability and surface hardness.
[0004] Although the above-mentioned method can achieve both surface robustness and formability, generally, when the sheet is thermoformed, the protective film attached to the hard coat layer is peeled off before molding. This leaves the semi-cured hard coat layer exposed during the process, which can lead to adhesion of foreign matter to the surface due to static electricity and numerous scratches during handling, adversely affecting the product appearance.
[0005] Furthermore, Patent Document 2 proposes protective films made of various materials with adhesives so that the protective film can be molded while still attached. However, if the materials of the base sheet and the protective film are different, the deformation behavior during thermoforming will differ, resulting in problems such as warping of the sheet and partial peeling of the protective film. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] JP 2012-210755 A [Patent Document 2] JP 2020-90084 A Summary of the Invention [Problem to be solved by the invention]
[0007] The object of the present invention is to provide a thermoforming sheet or decorative sheet having excellent surface appearance that combines moldability and hardness, and a molded article using the same with a high yield. In particular, the object of the present invention is to provide a thermoforming sheet or decorative sheet with a protective film suitable for use in a method of integrating a sheet having chemical resistance and abrasion resistance with a resin molded article by thermoforming in order to impart these functions to the surface of the resin molded article, and a molded article using the same. [Means for solving the problem]
[0008] It has been discovered that the above-mentioned problems can be solved by a thermoforming sheet with a protective film, which is formed by laminating at least four layers in this order: a layer (A layer) containing a polycarbonate-based resin, a layer (B layer) containing an acrylic-based resin, a layer (C layer) formed from an uncured product of an acrylate-based active energy ray-curable resin composition (composition C), and a protective film layer (D layer) containing a polycarbonate-based resin. That is, according to the present invention, the following configurations are provided.
[0009] 1. A molding sheet with a protective film, comprising at least four layers laminated in this order: a layer containing a polycarbonate-based resin (layer A), a layer containing an acrylic-based resin (layer B), a layer (layer C) formed from an uncured product of an acrylate-based active energy ray-curable resin composition (composition C), and a protective film layer (layer D) containing a polycarbonate-based resin, wherein the glass transition temperatures (Tg) of layer A and layer D are 100°C or higher and 145°C or lower, and the absolute value of the difference in glass transition temperatures between layer A and layer D is 20°C or lower.
[0010] 2. The thermoforming sheet with protective film according to the preceding paragraph 1, wherein the A layer and the D layer contain a polyester-based thermoplastic elastomer, the polyester-based thermoplastic elastomer being composed of a hard segment composed of a polybutylene terephthalate unit and a soft segment composed of a polyester unit having an aromatic dicarboxylic acid and an aliphatic dicarboxylic acid as the dicarboxylic acid component and a diol having 5 to 15 carbon atoms as the diol component.
[0011] 3. The thermoforming sheet with a protective film according to the above item 2, wherein the layers A and D contain 1 to 20 parts by weight of a polyester thermoplastic elastomer per 100 parts by weight of a polycarbonate resin.
[0012] 4. The thermoforming sheet with a protective film according to any one of the above items 1 to 3, wherein the layer C and the layer D are in direct contact with each other without any other layer therebetween.
[0013] 5. The thermoforming sheet with protective films according to any one of items 1 to 4 above, wherein the total thickness of the forming sheet with protective films is in the range of 0.05 mm or more and 3 mm or less.
[0014] 6. A decorative sheet with a protective film, comprising the protective film-attached thermoforming sheet according to any one of items 1 to 5 above, and a decorative layer formed on the side of layer A opposite to the side of layers B, C and D.
[0015] 7. A method for producing a molded body, comprising forming a thermoforming sheet with a protective film as described in any one of items 1 to 5 above or a decorative sheet with a protective film as described in item 6 above into the shape of a mold cavity in advance, placing the sheet in the mold, and producing a molded body by integrating the sheet with the protective film at the same time as molding a resin material, and then post-exposing the sheet to active energy rays, followed by peeling off the layer D.
[0016] 8. A method for producing a molded body, comprising attaching the thermoforming sheet with a protective film described in any one of the preceding items 1 to 5 or the decorative sheet with a protective film described in any one of the preceding items 6 to the cavity side of a mold under vacuum pressure, producing a molded body in which the sheet is integrated with the resin material at the same time as the resin material is molded, and then post-exposing the sheet to active energy rays, followed by peeling off the layer D. Effect of the Invention
[0017] The thermoforming sheet or decorative sheet with a protective film of the present invention is a thermoforming sheet or decorative sheet with a protective film that has excellent formability, hardness, and surface appearance that can improve process yield, and is particularly suitable for use in a technique in which a sheet to which these functions have been imparted is integrated with a resin molded product by thermoforming in order to impart chemical resistance and abrasion resistance to the surface of the resin molded product. Resin molded products using these can be used for automobile interior materials, electrical appliances, cosmetic cases, building material interior and exterior products, etc., and the industrial effects they provide are exceptional. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0018] The present invention will be described in detail below.
[0019] (Layer containing polycarbonate resin (Layer A)) The polycarbonate resin used in the layer A of the present invention is a polymer in which dihydroxy compounds are bonded by carbonate ester bonds, and is usually obtained by reacting a dihydroxy component with a carbonate precursor by interfacial polymerization or melt polymerization.
[0020] Representative examples of dihydroxy components include 2,2-bis(4-hydroxyphenyl)propane (commonly known as bisphenol A), 2,2-bis{(4-hydroxy-3-methyl)phenyl}propane (bisphenol C), 2,2-bis(4-hydroxyphenyl)butane, 2,2-bis(4-hydroxyphenyl)-3-methylbutane, 2,2-bis(4-hydroxyphenyl)-3,3-dimethylbutane, 2,2-bis(4-hydroxyphenyl)-4-methylpentane, and 1,1-bis(4-hydroxyphenyl)cyclohexane. Examples of the bisphenols include cyclohexane, 1,1-bis(4-hydroxyphenyl)-3,3,5-trimethylcyclohexane, 1,1-bis(4-hydroxyphenyl)octane, 1,1-bis(4-hydroxyphenyl)decane, 9,9-bis{(4-hydroxy-3-methyl)phenyl}fluorene, 9,9-bis(4-hydroxyphenyl)fluorene, α,α'-bis(4-hydroxyphenyl)-m-diisopropylbenzene, isosorbide, 1,3-propanediol, 1,4-butanediol, and 1,6-hexanediol. These may be homopolymers using one of them alone, or copolymers of two or more of them. From the viewpoints of physical properties and cost, bisphenol A is preferred. In the present invention, polycarbonates in which 50 mol % or more of the bisphenol component is bisphenol A and / or bisphenol C are preferred, more preferably 70 mol % or more, and even more preferably 90 mol % or more.
[0021] Specific examples of polycarbonates include homopolymers of bisphenol A, homopolymers of bisphenol C, copolymers of bisphenol A and bisphenol C, copolymers of bisphenol A and 1,1-bis(4-hydroxyphenyl)-3,3,5-trimethylcyclohexane, copolymers of bisphenol A and 9,9-bis{(4-hydroxy-3-methyl)phenyl}fluorene, etc. The homopolymers of bisphenol A are most preferred.
[0022] The carbonate precursor may be a carbonyl halide, a carbonate ester or a haloformate, and specific examples thereof include phosgene, diphenyl carbonate or a dihaloformate of a dihydric phenol.
[0023] When the dihydric dihydroxy compound and the carbonate precursor are reacted by the interfacial polymerization method or the melt polymerization method to produce the polycarbonate resin, a catalyst, a terminal terminator, an antioxidant for the dihydric phenol, etc. may be used as necessary. The polycarbonate resin may be a branched polycarbonate resin copolymerized with a trifunctional or higher polyfunctional aromatic compound, a polyester carbonate resin copolymerized with an aromatic or aliphatic difunctional carboxylic acid, or a mixture of two or more of the obtained polycarbonate resins.
[0024] The molecular weight of the polycarbonate resin is preferably in the range of 13,000 to 40,000, expressed as a viscosity average molecular weight. If the molecular weight is lower than 13,000, the sheet may become brittle and may easily crack or burr during thermoforming, while if it is higher than 40,000, the melt viscosity of the resin composition with a polyester thermoplastic elastomer may become too high, making melt film formation difficult. The molecular weight is more preferably 15,000 to 35,000, even more preferably 20,000 to 32,000, and particularly preferably 22,000 to 28,000. In the case of a mixture of two or more polycarbonate resins, the molecular weight is represented by the molecular weight of the entire mixture. Here, the viscosity average molecular weight is the specific viscosity (η) at 20°C of a solution in which 0.7 g of polycarbonate is dissolved in 100 mL of methylene chloride. sp ) was measured, and the viscosity average molecular weight (M) was calculated according to the following formula:
[0025] η sp / c=[η]+0.45×[η] 2 c [η]=1.23×10 -4 M 0.83 (where c=0.7g / dL, [η] is the intrinsic viscosity)
[0026] The glass transition temperature of the layer (A layer) containing the polycarbonate resin of the present invention must be in the range of 100°C to 145°C, preferably 110°C to 140°C, more preferably 120°C to 130°C. If the glass transition temperature is higher than the above range, the thermoforming temperature must be increased, and the heat exposure during thermoforming causes thermal radical polymerization of the layer (C layer) formed from the uncured product of the acrylate-based active energy ray curable resin composition (composition C), resulting in poor appearance such as cracks after molding. If the glass transition temperature is lower than the above range, the molding temperature appropriate for thermoforming of the A layer will be lower than the glass transition temperature of the layer (B layer) containing the acrylic resin or the layer (C layer) formed from the uncured product of the acrylate-based active energy ray curable resin composition (composition C), making it impossible to thermoform. Here, the glass transition temperature refers to a value measured by differential scanning calorimetry (DSC).
[0027] The method for adjusting the glass transition temperature of the A layer is not particularly limited, but in order to ensure the transparency of the thermoforming sheet, a method of blending a polyester thermoplastic elastomer with a polycarbonate resin is preferred. The polyester thermoplastic elastomer is preferably a multiblock copolymer composed of a hard segment composed of a polybutylene terephthalate unit and a soft segment composed of a polyester unit having an aromatic dicarboxylic acid and an aliphatic dicarboxylic acid as a dicarboxylic acid component and a diol having 5 to 15 carbon atoms as a diol component.
[0028] The hard segment consisting of the polybutylene terephthalate unit has excellent compatibility with polycarbonate resin, is preferable in terms of transparency and thermoformability, and has good properties in terms of strength, etc. Polybutylene terephthalate may contain other components as copolymerization components within a range that does not impair the effects of the present invention. The proportion of such copolymerization components is preferably 30 mol % or less, more preferably 20 mol % or less, and even more preferably 10 mol % or less, of the total components of both the dicarboxylic acid component and the diol component, each of which is 100 mol %. The intrinsic viscosity of the polymer that becomes the hard segment is preferably in the range of 0.2 to 2.0, more preferably 0.5 to 1.5.
[0029] The soft segment consisting of polyester units having aromatic dicarboxylic acid and aliphatic dicarboxylic acid as dicarboxylic acid components and diol having 5 to 15 carbon atoms as diol components refers to a segment in which the melting point of the polymer formed from the segment is 100°C or less, or the polymer is liquid and amorphous at 100°C. The intrinsic viscosity of the polymer to be the soft segment is preferably in the range of 0.2 to 2.0, more preferably 0.5 to 1.5. The soft segment used is a soft segment consisting of polyester units having aromatic dicarboxylic acid and / or aliphatic carboxylic acid as dicarboxylic acid components and diol having 5 to 15 carbon atoms as diol components (hereinafter sometimes referred to as "SS-1"). SS-1 is suitable because it provides very good transparency.
[0030] In the soft segment SS-1, in order to obtain better transparency, the content of aromatic dicarboxylic acid is preferably 60 to 99 mol % and the content of aliphatic dicarboxylic acid is preferably 1 to 40 mol % in a total of 100 mol % of dicarboxylic acid components. The content of aromatic dicarboxylic acid is more preferably 70 to 95 mol % and the content of aliphatic dicarboxylic acid is 5 to 30 mol %. The content of aromatic dicarboxylic acid is further preferably 85 to 93 mol % and the content of aliphatic dicarboxylic acid is 7 to 15 mol %. The content of aromatic dicarboxylic acid is particularly preferably 89 to 92 mol % and the content of aliphatic dicarboxylic acid is particularly preferably 8 to 11 mol %.
[0031] The aromatic dicarboxylic acid of SS-1 is preferably at least one selected from the group consisting of terephthalic acid, isophthalic acid, 1,5-naphthalenedicarboxylic acid, 2,6-naphthalenedicarboxylic acid, 4,4'-diphenylcarboxylic acid, bis(4-carboxyphenyl)methane, and bis(4-carboxyphenyl)sulfone, with terephthalic acid and isophthalic acid being more preferred, and isophthalic acid being particularly preferred from the viewpoint of reduced crystallinity.
[0032] As the aliphatic dicarboxylic acid of SS-1, linear aliphatic dicarboxylic acids having 4 to 12 carbon atoms such as succinic acid, adipic acid, and sebacic acid are preferred, with sebacic acid being particularly preferred.
[0033] As the diol component having 5 to 15 carbon atoms in SS-1, linear aliphatic diols having 6 to 12 carbon atoms such as hexamethylene glycol, decamethylene glycol, 3-methylpentanediol, and 2-methyloctamethylenediol are more preferred, with hexamethylene glycol being particularly preferred.
[0034] SS-1 is particularly preferred from the viewpoints that it has high compatibility with polycarbonate resins, can produce a highly transparent product, and has good surface properties and transparency after thermoforming. More specifically, SS-1 is preferably a polyester made of isophthalic acid, sebacic acid, and hexamethylene glycol.
[0035] In the present invention, the ratio of hard segments to soft segments in the polyester thermoplastic elastomer is preferably 20-70% by weight for hard segments and 80-30% by weight for soft segments, more preferably 20-40% by weight for hard segments and 80-60% by weight for soft segments, based on 100% by weight of the elastomer. The intrinsic viscosity of the polyester thermoplastic elastomer (measured in o-chlorophenol at 35°C) is preferably 0.6 or more, more preferably 0.8-1.5, and even more preferably 0.8-1.2. If the intrinsic viscosity is lower than the above range, the sheet strength may decrease, which is not preferable.
[0036] In the present invention, it is preferable that 1 to 20 parts by weight of polyester thermoplastic elastomer is contained per 100 parts by weight of polycarbonate resin in layer A. If the amount of polyester thermoplastic elastomer is less than 1 part by weight, the glass transition temperature of layer A may exceed 145°C, whereas if it exceeds 20 parts by weight, the glass transition temperature of layer A may fall below 100°C.
[0037] The thickness of layer A is preferably in the range of 20 to 3000 μm, more preferably in the range of 30 to 2500 μm, further preferably in the range of 40 to 2000 μm, particularly preferably in the range of 50 to 1500 μm, and most preferably in the range of 100 to 1000 μm.
[0038] The layer A of the present invention may contain various additives that are generally used in each resin. For example, heat stabilizers, antioxidants, ultraviolet absorbers, antistatic agents, dyes, etc. Furthermore, it may contain reinforcing fillers such as glass fibers within a range that does not impair the effects of the present invention.
[0039] (Layer containing acrylic resin (Layer B)) In the present invention, the acrylic resin used in the B layer is preferably one mainly composed of a polymer of a methacrylic acid ester or an acrylic acid ester. When a resin other than an acrylic resin is used as the B layer, for example, a polycarbonate resin is not preferred because the surface hardness of the laminated film is low and the molded body is easily scratched. In addition, a PET resin is not preferred because it is prone to cause poor appearance due to uneven thickness. The acrylic resin is preferably a copolymer containing methyl methacrylate at preferably 50 mol % or more, more preferably 70 mol % or more, even more preferably 80 mol % or more, and particularly preferably 90 mol % or more.
[0040] Examples of other copolymerization components include ethyl methacrylate, butyl methacrylate, 2-ethylhexyl methacrylate, methyl acrylate, ethyl acrylate, butyl acrylate, and 2-ethylhexyl acrylate. Examples of other copolymerization components include other ethylenically unsaturated monomers. Specifically, examples of vinyl aromatic compounds such as styrene, α-methylstyrene, and vinyltoluene, diene compounds such as 1,3-butadiene and isoprene, alkenyl cyan compounds such as acrylonitrile and methacrylonitrile, acrylic acid, methacrylic acid, maleic anhydride, and N-substituted maleimide are listed. These may be used alone or in combination of two or more. The content of the copolymerization component is preferably 0 to 50% by weight, more preferably 0 to 30% by weight, and even more preferably 0 to 20% by weight. Methods for producing acrylic resins are generally roughly divided into emulsion polymerization, suspension polymerization, and continuous polymerization, and the acrylic resin used in the present invention may be produced by any of these polymerization methods. Layer B may contain various additives such as general heat stabilizers, colorants, release agents, lubricants, antistatic agents, and matting agents.
[0041] Although rubber particles may be added to the layer B of the present invention, it is preferable that the layer B does not substantially contain rubber particles. Although the addition of rubber particles to an acrylic resin to improve toughness is a well-known technique and is widely used, it is preferable that the layer B does not contain rubber particles from the viewpoint of ensuring transparency and surface hardness.
[0042] The thickness of layer B is preferably in the range of 5 to 300 μm, more preferably in the range of 8 to 250 μm, further preferably in the range of 10 to 200 μm, particularly preferably in the range of 20 to 150 μm, and most preferably in the range of 30 to 100 μm.
[0043] (Layer (C layer) formed from an uncured product of the acrylate-based active energy ray-curable resin composition (composition C)) The uncured product of the active energy ray curable resin composition (composition C) constituting the layer C of the present invention contains an acrylate-based resin such as acrylate or urethane acrylate. The content is preferably in the range of 70 to 95% by weight of the total solid content of the layer C. If it is less than 70% by weight, the cohesive strength, chemical resistance, scratch resistance, optical properties, etc. of the coating film may decrease. If it exceeds 95% by weight, the initiation of photopolymerization may be delayed, resulting in poor productivity.
[0044] The acrylate resin contained in the layer C in the present invention may be either an oligomer or a prepolymer, and is not particularly limited.
[0045] The glass transition temperature of the uncured acrylate resin composition (composition C) is preferably 30 to 150°C, more preferably 35 to 140°C, and is preferably 40 to 130°C. It is particularly preferable that the glass transition temperature is less than 30°C. If an acrylate resin with a glass transition temperature of less than 30°C is used, the coating film in the uncured state after heat drying may have tackiness, and blocking may easily occur when the resin is wound into a roll. If the glass transition temperature is more than 150°C, sufficient heat may not be applied during molding, and cracks may occur.
[0046] In addition, the uncured acrylate resin composition (composition C) is irradiated with active energy rays such as ultraviolet rays and cured, and the resulting cured layer preferably has a pencil hardness of H or more. By setting the pencil hardness within this range, there is an advantage in that the abrasion resistance is improved. When the pencil hardness is H or more, the scratch resistance is sufficient.
[0047] Here, the pencil hardness is the value measured by applying an uncured acrylate resin composition (composition C) to a sheet and drying the sheet with an integrated light dose of 1000 mJ / cm as described later in the Examples. 2 The coating is irradiated with ultraviolet light at 400 V, cured to prepare a test piece, and the pencil hardness of the coating is measured in accordance with JIS K5600-5-4-1999.
[0048] In the present invention, a photopolymerization initiator can be contained in the C layer. By containing a photopolymerization initiator, the polymerization and curing reaction of the hard coat layer by irradiation with light (ultraviolet rays) can be carried out in a short time. Examples of the photopolymerization initiator include benzophenone, benzil, Michler's ketone, 2-chlorothioxanthone, 2,4-diethylthioxanthone, benzoin ethyl ether, benzoin isopropyl ether, benzoin isobutyl ether, 2,2-diethoxyacetophenone, benzil dimethyl ketal, 2,2-dimethoxy-1,2-diphenylethane-1-one, 2-hydroxy-2-methyl-1-phenylpropan-1-one, 1-hydroxycyclohexyl phenyl ketone, 2-methyl-1-[4-(methylthio) phenyl]-2-morpholinopropanone-1, 1-[4-(2-hydroxyethoxy)-phenyl]-2-hydroxy-2-methyl-1-propan-1-one, bis(cyclopentadienyl)-bis(2,6-difluoro-3-(pyr-1-yl)titanium, 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-butanone-1, 2,4,6-trimethylbenzoyldiphenylphosphine oxide, and the like. These compounds may be used alone or in combination.
[0049] The photopolymerization initiator contained in the solid content of the C layer is preferably 0.01 to 10% by weight, more preferably 0.1 to 5% by weight, based on the total solid content of the C layer. If the content of the photopolymerization initiator is less than 0.01% by weight, the photocurability may decrease, and if it is blended in more than 10% by weight, coloring of the C layer may occur, and the progress of the photocuring reaction may not change, which may be economically disadvantageous. In addition, it is also possible to add various known dyes and sensitizers to improve the photocurability.
[0050] The thickness of the C layer is preferably in the range of 1 to 50 μm, more preferably in the range of 2 to 30 μm, further preferably in the range of 2.5 to 20 μm, and particularly preferably in the range of 3 to 10 μm.
[0051] Depending on the circumstances, additives such as a leveling agent, an antifoaming agent, an antifouling agent, or other surfactants, a surface modifier, or an organic filler, an inorganic filler, or other fillers may be added to the C layer.
[0052] (Protective film layer containing polycarbonate resin (Layer D)) The polycarbonate resin used in the layer D of the present invention is a polymer in which dihydroxy compounds are bonded by carbonate ester bonds, and is usually obtained by reacting a dihydroxy component with a carbonate precursor by interfacial polymerization or melt polymerization.
[0053] Representative examples of dihydroxy components are 2,2-bis(4-hydroxyphenyl)propane (commonly known as bisphenol A), 2,2-bis{(4-hydroxy-3-methyl)phenyl}propane, nyl}propane (bisphenol C), 2,2-bis(4-hydroxyphenyl)butane, 2,2-bis(4-hydroxyphenyl)-3-methylbutane, 2,2-bis(4-hydroxyphenyl)-3,3-dimethylbutane, 2,2-bis(4-hydroxyphenyl)-4-methylpentane, 1,1-bis(4-hydroxyphenyl)cyclohexane, 1,1-bis(4-hydroxyphenyl)-3,3,5-trimethylcyclohexane, 1,1-bis(4-hydroxyphenyl)octane, 1,1-bis(4-hydroxyphenyl)decane, 9,9-bis{(4-hydroxy-3-methyl)phenyl}fluorene, 9,9-bis(4-hydroxyphenyl)fluorene, α,α'-bis(4-hydroxyphenyl)-m-diisopropylbenzene, isosorbide, 1,3-propanediol, 1,4-butanediol, 1,6-hexanediol, and the like. These may be homopolymers using one of them alone, or copolymers in which two or more types are copolymerized. In terms of physical properties and cost, bisphenol A is preferred. In the present invention, polycarbonates in which 50 mol % or more of the bisphenol component is bisphenol A and / or bisphenol C are preferred, more preferably 70 mol % or more, and even more preferably 90 mol % or more.
[0054] Specific examples of polycarbonates include homopolymers of bisphenol A, homopolymers of bisphenol C, copolymers of bisphenol A and bisphenol C, copolymers of bisphenol A and 1,1-bis(4-hydroxyphenyl)-3,3,5-trimethylcyclohexane, copolymers of bisphenol A and 9,9-bis{(4-hydroxy-3-methyl)phenyl}fluorene, etc. The homopolymers of bisphenol A are most preferred.
[0055] The carbonate precursor may be a carbonyl halide, a carbonate ester or a haloformate, and specific examples thereof include phosgene, diphenyl carbonate or a dihaloformate of a dihydric phenol.
[0056] When the dihydric dihydroxy compound and the carbonate precursor are reacted by the interfacial polymerization method or the melt polymerization method to produce the polycarbonate resin, a catalyst, a terminal terminator, an antioxidant for the dihydric phenol, etc. may be used as necessary. The polycarbonate resin may be a branched polycarbonate resin copolymerized with a trifunctional or higher polyfunctional aromatic compound, a polyester carbonate resin copolymerized with an aromatic or aliphatic difunctional carboxylic acid, or a mixture of two or more of the obtained polycarbonate resins.
[0057] The molecular weight of the polycarbonate resin is preferably in the range of 13,000 to 40,000, expressed as a viscosity average molecular weight. If the molecular weight is lower than 13,000, the sheet may become brittle and may easily crack or burr during thermoforming, while if it is higher than 40,000, the melt viscosity of the resin composition with a polyester thermoplastic elastomer may become too high, making melt film formation difficult. The molecular weight is more preferably 15,000 to 35,000, even more preferably 20,000 to 32,000, and particularly preferably 22,000 to 28,000. In the case of a mixture of two or more polycarbonate resins, the molecular weight is represented by the molecular weight of the entire mixture. Here, the viscosity average molecular weight is the specific viscosity (η) at 20°C of a solution in which 0.7 g of polycarbonate is dissolved in 100 mL of methylene chloride. sp ) was measured, and the viscosity average molecular weight (M) was calculated according to the following formula:
[0058] η sp / c=[η]+0.45×[η] 2 c [η]=1.23×10 -4 M 0.83 (where c=0.7g / dL, [η] is the intrinsic viscosity)
[0059] The glass transition temperature of the protective film layer (D layer) containing the polycarbonate-based resin of the present invention is It is necessary that the temperature is in the range of 100°C or more and 145°C or less, preferably 110°C or more and 140°C or less, more preferably 120°C or more and 130°C or less. If the glass transition temperature is higher than the above range, the thermoforming temperature needs to be increased, and the heat exposure during thermoforming causes thermal radical polymerization of the layer (C layer) formed from the uncured product of the acrylate-based active energy ray curable resin composition (composition C), resulting in poor appearance such as cracks after molding. If the glass transition temperature is lower than the above range, the molding temperature appropriate for thermoforming of the D layer falls below the glass transition temperature of the layer (B layer) containing an acrylic resin or the layer (C layer) formed from the uncured product of the acrylate-based active energy ray curable resin composition (composition C), making it impossible to thermoform. Here, the glass transition temperature refers to a value measured by differential scanning calorimetry (DSC).
[0060] The method for adjusting the glass transition temperature of the layer D is not particularly limited, but a method of blending a polyester thermoplastic elastomer with a polycarbonate resin is preferred, as in the case of the layer A. The polyester thermoplastic elastomer is preferably a multiblock copolymer composed of a hard segment made of a polybutylene terephthalate unit and a soft segment made of a polyester unit having an aromatic dicarboxylic acid and an aliphatic dicarboxylic acid as the dicarboxylic acid component and a diol having 5 to 15 carbon atoms as the diol component.
[0061] The hard segment consisting of the polybutylene terephthalate unit has excellent compatibility with polycarbonate resin, is preferable in terms of transparency and thermoformability, and has good properties in terms of strength, etc. Polybutylene terephthalate may contain other components as copolymerization components within a range that does not impair the effects of the present invention. The proportion of such copolymerization components is preferably 30 mol % or less, more preferably 20 mol % or less, and even more preferably 10 mol % or less, of the total components of both the dicarboxylic acid component and the diol component, each of which is 100 mol %. The intrinsic viscosity of the polymer that becomes the hard segment is preferably in the range of 0.2 to 2.0, more preferably 0.5 to 1.5.
[0062] The soft segment consisting of polyester units having aromatic dicarboxylic acid and aliphatic dicarboxylic acid as dicarboxylic acid components and diol having 5 to 15 carbon atoms as diol components refers to a segment in which the melting point of the polymer formed from the segment is 100°C or less, or the polymer is liquid and amorphous at 100°C. The intrinsic viscosity of the polymer to be the soft segment is preferably in the range of 0.2 to 2.0, more preferably 0.5 to 1.5. The soft segment used is a soft segment consisting of polyester units having aromatic dicarboxylic acid and / or aliphatic carboxylic acid as dicarboxylic acid components and diol having 5 to 15 carbon atoms as diol components (hereinafter sometimes referred to as "SS-1"). SS-1 is suitable because it provides very good transparency.
[0063] In the soft segment SS-1, in order to obtain better transparency, the content of aromatic dicarboxylic acid is preferably 60 to 99 mol % and the content of aliphatic dicarboxylic acid is preferably 1 to 40 mol % in a total of 100 mol % of dicarboxylic acid components. The content of aromatic dicarboxylic acid is more preferably 70 to 95 mol % and the content of aliphatic dicarboxylic acid is 5 to 30 mol %. The content of aromatic dicarboxylic acid is further preferably 85 to 93 mol % and the content of aliphatic dicarboxylic acid is 7 to 15 mol %. The content of aromatic dicarboxylic acid is particularly preferably 89 to 92 mol % and the content of aliphatic dicarboxylic acid is particularly preferably 8 to 11 mol %.
[0064] The aromatic dicarboxylic acid of SS-1 is preferably at least one selected from the group consisting of terephthalic acid, isophthalic acid, 1,5-naphthalenedicarboxylic acid, 2,6-naphthalenedicarboxylic acid, 4,4'-diphenylcarboxylic acid, bis(4-carboxyphenyl)methane and bis(4-carboxyphenyl)sulfone. and isophthalic acid are more preferred, with isophthalic acid being particularly preferred from the standpoint of reduced crystallinity.
[0065] As the aliphatic dicarboxylic acid of SS-1, linear aliphatic dicarboxylic acids having 4 to 12 carbon atoms such as succinic acid, adipic acid, and sebacic acid are preferred, with sebacic acid being particularly preferred.
[0066] As the diol component having 5 to 15 carbon atoms in SS-1, linear aliphatic diols having 6 to 12 carbon atoms such as hexamethylene glycol, decamethylene glycol, 3-methylpentanediol, and 2-methyloctamethylenediol are more preferred, with hexamethylene glycol being particularly preferred.
[0067] SS-1 is particularly preferred from the viewpoints that it has high compatibility with polycarbonate resins, can produce a highly transparent product, and has good surface properties and transparency after thermoforming. More specifically, SS-1 is preferably a polyester made of isophthalic acid, sebacic acid, and hexamethylene glycol.
[0068] In the present invention, the ratio of hard segments to soft segments in the polyester thermoplastic elastomer is preferably 20-70% by weight for hard segments and 80-30% by weight for soft segments, more preferably 20-40% by weight for hard segments and 80-60% by weight for soft segments, based on 100% by weight of the elastomer. The intrinsic viscosity of the polyester thermoplastic elastomer (measured in o-chlorophenol at 35°C) is preferably 0.6 or more, more preferably 0.8-1.5, and even more preferably 0.8-1.2. If the intrinsic viscosity is lower than the above range, the sheet strength may decrease, which is not preferable.
[0069] In the present invention, it is preferable that 1 to 20 parts by weight of polyester thermoplastic elastomer is contained per 100 parts by weight of polycarbonate resin in layer D. If the amount of polyester thermoplastic elastomer is less than 1 part by weight, the glass transition temperature of layer D may exceed 145°C, whereas if it exceeds 20 parts by weight, the glass transition temperature of layer D may fall below 100°C.
[0070] The thickness of layer D is preferably in the range of 10 to 100 μm, more preferably in the range of 15 to 50 μm, and most preferably in the range of 150 to 30 μm.
[0071] In the present invention, it is preferable that the C layer and the D layer are in direct contact with each other without any other layer such as an adhesive layer therebetween, since this provides better moldability and improves the surface appearance of the resulting molded article.
[0072] The layer D of the present invention may contain various additives that are generally used in each resin, such as heat stabilizers, antioxidants, UV absorbers, antistatic agents, dyes, etc. Furthermore, it may contain reinforcing fillers such as glass fibers, within the scope of not impairing the effects of the present invention.
[0073] (Difference in glass transition temperature between layers A and D) It is essential that the absolute value of the glass transition temperature difference between the A layer and the D layer of the present invention is 20° C. or less. If the absolute value of the glass transition temperature difference is greater than 20° C., the deformation behavior during thermoforming will differ, causing partial peeling between the D layer and the C layer, or causing the sheet to warp significantly after molding. The absolute value of the glass transition temperature difference between the A layer and the D layer is preferably 15° C. or less, more preferably 10° C. or less.
[0074] (Method of manufacturing thermoforming sheet with protective film) The laminated sheet of layer A and layer B constituting the thermoforming sheet of the present invention is made of molding material A for layer A, Molding material B for layer B can be produced by the co-extrusion method. The co-extrusion method is a method in which molding materials A and B are melt-extruded using separate extruders and laminated using a feed block or multi-manifold die to obtain a multi-layer sheet, and the total thickness and thickness composition of the resulting laminated sheet can be controlled by adjusting the extrusion rate and film-forming speed of each extruder, the die slip interval, etc.
[0075] The laminated sheet is formed by pressing the molten resin against a roll or belt. Furthermore, the molten resin before it cools and solidifies can be pressed with a metal roll to transfer a metal mirror surface, improving the surface appearance of the laminated sheet. Examples of the metal elastic roll include a shaft roll and a cylindrical metal thin film arranged to cover the outer circumferential surface of the shaft roll and in contact with the molten resin, in which a temperature-controlled fluid such as water or oil is sealed between the shaft roll and the metal thin film, and a rubber roll with a metal belt wound around its surface. Among them, a metal elastic roll with a metal belt wound around two or more rolls can press the molten resin against a wider surface on a circular arc, thereby cooling the resin in a state in which as little stress remains as possible.
[0076] A coating method is generally used to laminate the C layer constituting the thermoforming sheet of the present invention on the laminated sheet of the A layer and the B layer. The coating method is not particularly limited, but coating can be performed by a method that makes it easy to adjust the coating thickness, such as gravure coating, microgravure coating, fountain bar coating, slide die coating, and slot die coating. In the coating process, a coating material in which an acrylate-based active energy ray curable resin composition (composition C) and, if necessary, a hindered amine-based compound, an initiator, and other additives are dissolved and dispersed in an appropriate solvent is applied onto the laminated sheet and dried to form the C layer. The solvent can be appropriately selected depending on the solubility of composition C, and it is sufficient that it is a solvent that can uniformly dissolve or disperse at least the solid contents (resin, polymerization initiator, and other additives). Examples of such solvents include ketones (acetone, methyl ethyl ketone, methyl isobutyl ketone, cyclohexanone, etc.), ethers (dioxane, tetrahydrofuran, etc.), aliphatic hydrocarbons (hexane, etc.), alicyclic hydrocarbons (cyclohexane, etc.), aromatic hydrocarbons (toluene, xylene, etc.), halogenated carbons (dichloromethane, dichloroethane, etc.), esters (methyl acetate, ethyl acetate, butyl acetate, etc.), alcohols (methanol, ethanol, isopropanol, butanol, cyclohexanol, etc.), cellosolves (methyl cellosolve, ethyl cellosolve, etc.), cellosolve acetates, sulfoxides, amides, etc. The solvents may be used alone or in combination.
[0077] Thermal lamination is suitable for laminating the protective film layer (layer D) of the present invention. By increasing the lamination temperature above the glass transition temperature of layer C, layer C softens and is welded to layer D, providing the desired interfacial adhesive strength.
[0078] The thickness of the thermoforming sheet with a protective film of the present invention is not particularly limited, but is preferably 0.05 mm or more and 3 mm or less, more preferably 0.1 mm or more and 2.5 mm or less, even more preferably 0.15 mm or more and 2 mm or less, and particularly preferably 0.2 mm or more and 1 mm or less.
[0079] (Method of manufacturing decorative sheet) In the thermoforming sheet with protective film of the present invention, a decorative layer can be provided by printing or the like on the side of Layer A opposite Layer B. Methods for forming the decorative layer include forming a pattern layer by printing, forming a thin film layer of metal or metal oxide, and the like, and these may be used in combination. As a printing method for forming the pattern layer, known printing methods such as gravure printing, lithographic printing, flexographic printing, dry offset printing, pad printing, and screen printing can be used depending on the product shape and printing purpose. Methods for forming a thin film layer of metal or metal oxide include vapor deposition, thermal spraying, plating, and the like. Specific vapor deposition methods include vacuum vapor deposition, stripping, and the like. Examples of the method include sputtering, ion plating, thermal CVD, plasma CVD, and photo CVD. Examples of the thermal spraying method include atmospheric plasma spraying and reduced pressure plasma spraying. Examples of the plating method include electroless plating, hot-dip plating, and electric plating.
[0080] (Method of Manufacturing Molded Product) Molded articles can be produced using the thermoforming sheet or decorative sheet with a protective film of the present invention. Examples of the molded articles include automobile interior materials, automobile indicator panels, electrical appliances, cosmetic cases, interior and exterior building materials, cases for various devices, products, and miscellaneous items, switches, keys, keypads, handles, levers, buttons, and housings and exterior parts for home appliances and AV devices such as personal computers, mobile phones, and mobile devices.
[0081] The molded article can be obtained by carrying out various conventionally known molding processes using the thermoforming sheet or the decorative sheet with the protective film.
[0082] Examples of molding methods for molded bodies include the insert molding method, which is an in-mold decoration method for injection molding, in which a thermoforming sheet with a protective film or a decorative sheet that has been shaped in advance by vacuum forming, compressed air forming, or the like to fit the shape of the injection molding mold cavity is set in the mold, and molten resin is injected into it, and the thermoforming sheet with the protective film or the decorative sheet is welded to the resin molded product and integrated with it at the same time as the injection molding to obtain a molded body.
[0083] Another method for forming a molded product is to attach a thermoforming sheet or decorative sheet with a protective film to the side of a mold cavity using vacuum pressure, inject molten resin into it, and apply heat and pressure to bond the thermoforming sheet or decorative sheet with the protective film to a resin molded product to obtain a molded product.
[0084] Further, lamination by vacuum forming or compressed air forming can be used. Various methods can be used to heat the decorative forming film during thermoforming, such as infrared heaters, electric heaters, high-frequency induction, halogen lamps, microwaves, high-temperature derivatives (steam, etc.), and lasers.
[0085] The produced molded article is cooled or allowed to cool, and then the C layer is cured by irradiating it with radiation (ultraviolet rays, visible light, infrared rays, or electron beams). These radiations may be polarized or unpolarized. In particular, ultraviolet rays are preferred from the viewpoints of equipment costs, safety, running costs, etc. When curing is performed by irradiating ultraviolet rays, it is necessary to add a photopolymerization initiator. As the energy ray source of ultraviolet rays, for example, a high-pressure mercury lamp, a halogen lamp, a xenon lamp, a metal halide lamp, a nitrogen laser, an electron beam accelerator, a radioactive element, etc. are preferred. The irradiation dose of the energy ray source is 100 to 5,000 mJ / cm as the cumulative exposure dose at an ultraviolet wavelength of 365 nm. 2 The range is preferably 300 to 3,000 mJ / cm 2 More preferably, the irradiation dose is 100 mJ / cm 2 If it is less than 5,000 mJ / cm, curing may be insufficient and the hardness may decrease. 2If the oxygen concentration exceeds 100%, the C layer may become colored and the transparency may decrease. The oxygen concentration during radiation exposure is preferably 5% or less, more preferably 3% or less, and particularly preferably 2% or less. In the oxygen-free or low-concentration atmosphere, the gas contained other than oxygen is preferably an inert gas. Examples of the inert gas include nitrogen, helium, neon, and argon.
[0086] In addition, the protective film layer (layer D) can be peeled off after the layer C has cured. If an attempt is made to peel off layer D before the layer C has cured, there is a concern that a part of the uncured layer C may be transferred to layer D upon peeling, so it is preferable to peel off layer D after the layer C has cured. EXAMPLES
[0087] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples. Physical property measurements in the examples and comparative examples were carried out by the following methods.
[0088] (glass transition temperature) The measurement was performed using a TA Instruments 2920 DSC at a temperature rise rate of 20° C. / min, and the drop point was determined.
[0089] (Total thickness of thermoforming sheet) The value is the central value in the width direction of the sheet, measured with an electronic micro thickness meter manufactured by Anritsu Corp. The width direction of the sheet refers to the direction perpendicular to the sheet flow direction during film formation.
[0090] (Surface appearance of molded products) Using a biaxial stretching tester (manufactured by Toyo Seiki Co., Ltd.), the thermoforming sheet with the protective film was preheated for 1 minute at a temperature of 20°C above the glass transition temperature of the A layer, and then stretched at the same temperature to a stretch ratio of 1.3 times. An integrated light dose of 2000 mJ / cm was applied from the D layer side. 2 The C layer was cured by irradiating it with ultraviolet light at 400° C. Thereafter, the protective film (D layer) was peeled off, and the appearance of the sheet surface was evaluated according to the following criteria. △: Some scratches and slight surface deformation are observed. ×: Scratches and surface deformations observed
[0091] (Pencil hardness) The protective film (layer D) prepared in the above-mentioned evaluation of (surface appearance of molded article) was peeled off, and then the pencil hardness of the cured layer C of the sheet was measured in accordance with JIS K5600-5-4-1999.
[0092] (Moldability) Using a biaxial stretching tester (manufactured by Toyo Seiki Co., Ltd.), the thermoforming sheet with the protective film was preheated for 1 minute at a temperature of (glass transition temperature + 20) °C of layer A, and then stretched at the same temperature to a stretch ratio of 1.3 times. The appearance of the sheet was evaluated using the following criteria. ○: No cracks or cloudiness observed △: Weak cracks or slight cloudiness are observed ×: Cracks or cloudiness are observed
[0093] [Preparation Example 1] (Production of polyester-based thermoplastic elastomer) 100 parts by weight of dimethyl isophthalate, 13 parts by weight of dimethyl sebacate, and 80 parts by weight of hexamethylene glycol were subjected to an ester exchange reaction using a dibutyltin diacetate catalyst, followed by polycondensation under reduced pressure to obtain an amorphous polyester (soft segment) with an intrinsic viscosity of 1.06 and no endothermic peak due to melting of crystals when measured by the DSC method. 32 parts by weight of polybutylene terephthalate pellets (hard segment) with an intrinsic viscosity of 0.98 were added to 100 parts by weight of the polyester, and the mixture was further reacted at 240°C for 45 minutes, after which 0.03 parts by weight of phenylphosphonic acid was added to stop the reaction. The melting point of the obtained polymer was 190°C and the intrinsic viscosity was 0.93.
[0094] [Example 1] (Molding material A) Polycarbonate resin pellets (Teijin Limited, Panlite L1250WP (bisphenol A homopolycarbonate resin (PC-A, viscosity average molecular weight 23,900)) and the thermoplastic elastomer obtained in the above [Preparation Example 1] were each pre-dried in advance and mixed in a V-type blender so that 1 part by weight of thermoplastic elastomer was used per 100 parts by weight of polycarbonate resin pellets. The mixture was then extruded at a cylinder temperature of 260°C using a twin-screw extruder to form pellets, thereby obtaining molding material A for layer A. The glass transition temperature of molding material A was 145°C.
[0095] (Molding material B) As molding material B for layer B, an acrylic resin (Acrypet VH-001 manufactured by Mitsubishi Rayon Co., Ltd., an acrylic resin copolymerized with 95 mol % of methyl methacrylate and 5 mol % of methyl acrylate) was prepared.
[0096] (Co-extrusion) Molding materials A and B were each extruded from a 650 mm wide T-die using a feed block method with a single screw extruder with a screw diameter of 40 mm at cylinder temperatures of 260°C (molding material A), 250°C (molding material B), and screw rotation speeds of 109 rpm (molding material A), and 11 rpm (molding material B). The molten resin was then compressed between a metal roll and a metal sleeve roll and cooled, after which the edges were trimmed and the sheet was taken up at a take-up speed of 10.3 m / min to produce a 400 mm wide laminated sheet with a two-layer structure of A layer / B layer (layer A 440 μm, layer B 60 μm).
[0097] (Molding material D) Polycarbonate resin pellets (Panlite L1250WP (bisphenol A homopolycarbonate resin (PC-A), viscosity average molecular weight 23,900) manufactured by Teijin Limited) and the thermoplastic elastomer obtained in Preparation Example 1 above were each pre-dried in advance and mixed in a V-type blender so that 1 part by weight of thermoplastic elastomer was used per 100 parts by weight of polycarbonate resin pellets. The mixture was then extruded at a cylinder temperature of 260°C using a twin-screw extruder to form pellets, thereby obtaining molding material D for layer D. Molding material D had a glass transition temperature of 145°C.
[0098] (Protection film extrusion) Molding material D was extruded from a 650 mm wide T-die using a single-screw extruder with a screw diameter of 40 mm at a cylinder temperature of 260°C and a screw rotation speed of 54 rpm. The molten resin was then compressed between a metal roll and a metal sleeve roll and cooled. The edges were then trimmed and the resin was taken up at a take-up speed of 20.3 m / min to create a protective film layer (layer D) with a thickness of 50 μm and a width of 400 mm.
[0099] (Paint adjustment) The paint to form layer C was prepared by diluting 100 parts by weight of urethane acrylate ultraviolet curing resin "Folseed No. 371C (product name)" (solid content 40%, manufactured by Chugoku Paint Co., Ltd.), 5 parts by weight of Irgacure 184 (photopolymerization initiator, manufactured by Chiba Specialty Chemical Co., Ltd.), and 5 parts by weight of hindered amine compound TINUVIN 292 (product name)" (manufactured by BASF Ltd.) with methyl isobutyl ketone until the solid content concentration of the ultraviolet curing resin in the paint reached 30%, and then thoroughly stirring.
[0100] (Coating) The paint forming the above-mentioned C layer was applied to the B layer side of the laminated sheet of A layer and B layer using a bar coater (#8), and dried with hot air in a drying oven at 80°C for 1 minute to form a C layer with a coating thickness of 5 μm. Thereafter, a protective film (D layer) was placed on the C layer, and the layers were pressed between nip rolls heated to 100°C and heat laminated, and then cooled to produce a thermoforming sheet with a protective film of approximately 0.55 mm in thickness. The various evaluation results are shown in Table 1.
[0101] [Example 2] A 400 mm wide laminated sheet having a two-layer structure of A layer / B layer (A layer 120 μm, B layer 30 μm) was prepared in the (co-extrusion) process, and a thermoforming sheet with a protective film was prepared in the same manner as in Example 1, except that the contents of the thermoplastic elastomers in molding materials A and D were changed as shown in Table 1. The results of various evaluations are shown in Table 1.
[0102] [Example 3] A 400 mm wide laminated sheet having a two-layer structure of A layer / B layer (A layer 200 μm, B layer 50 μm) was prepared in the (co-extrusion) process, and a thermoforming sheet with a protective film was prepared in the same manner as in Example 1, except that the contents of the thermoplastic elastomers in molding materials A and D were changed as shown in Table 1. The results of various evaluations are shown in Table 1.
[0103] [Example 4] In the (co-extrusion) process, a 400 mm wide laminated sheet having a two-layer structure of A layer / B layer (A layer 40 μm, B layer 10 μm) was prepared, and a thermoforming sheet with a protective film was prepared in the same manner as in Example 1, except that the contents of the thermoplastic elastomers in molding materials A and D were changed as shown in Table 1. The results of various evaluations are shown in Table 1.
[0104] [Example 5] A 400 mm wide laminated sheet having a two-layer structure of A layer / B layer (A layer 360 μm, B layer 90 μm) was prepared in the (co-extrusion) process, and a thermoforming sheet with a protective film was prepared in the same manner as in Example 1, except that the contents of the thermoplastic elastomers in molding materials A and D were changed as shown in Table 1. The results of various evaluations are shown in Table 1.
[0105] [Example 6] In the production of the polycarbonate resin pellets of the molding material A, 2,2-bis{(4-hydroxy-3-methyl)phenyl}propane (commonly known as bisphenol C) was used instead of 2,2-bis(4-hydroxyphenyl)propane (commonly known as bisphenol A), and polycarbonate resin pellets not containing elastomer (PC-C, viscosity average molecular weight 21,500) were obtained and used as the molding material A for the A layer. In addition, in the (co-extrusion) process, a 400 mm wide laminated sheet having a two-layer structure of A layer / B layer (A layer 120 μm, B layer 30 μm) was prepared, and a thermoforming sheet with a protective film was prepared in the same manner as in Example 1, except that the content of the thermoplastic elastomer in the molding material D was changed as shown in Table 1. Various evaluation results are shown in Table 1.
[0106] [Example 7] Except for using a 100 μm thick adhesive layer in the (coating) step, a thermoforming sheet with a protective film was produced in the same manner as in Example 2. The results of various evaluations are shown in Table 1.
[0107] [Comparative Example 1] A thermoforming sheet with a protective film was produced in the same manner as in Example 1, except that no polyester-based thermoplastic elastomer was added to molding material A, a 400 mm-wide laminated sheet having a two-layer structure of layer A / layer B (layer A 2000 μm, layer B 450 μm) was produced in the (co-extrusion) process, and the content of the thermoplastic elastomer in molding material D was changed as shown in Table 1. The results of various evaluations are shown in Table 1.
[0108] [Comparative Examples 2 and 3] A 400 mm wide laminated sheet having a two-layer structure of A layer / B layer (A layer 760 μm, B layer 190 μm) was prepared in the (co-extrusion) process, and a thermoforming sheet with a protective film was prepared in the same manner as in Example 1, except that the contents of the thermoplastic elastomers in molding materials A and D were changed as shown in Table 1. The results of various evaluations are shown in Table 1.
[0109] [Comparative Example 4] In the (co-extrusion) process, a 400 mm wide laminated sheet having a two-layer structure of A layer / B layer (A layer 760 μm, B layer 190 μm) was prepared, and the thermoplastic elastomer content of molding material A was changed as shown in Table 1, and a thermoforming sheet was prepared in the same manner as in Example 1, except that no protective film (D layer) was laminated. Various evaluation results are shown in Table 1.
[0110] [Table 1] [Industrial Applicability]
[0111] The thermoforming sheet and decorative sheet of the present invention have excellent formability and hardness, and molded articles using the thermoforming sheet and decorative sheet are useful as automobile interior materials, automobile indicator panels, electrical appliances, cosmetic cases, interior and exterior building materials, cases for various devices, products, and miscellaneous items, switches, keys, keypads, handles, levers, buttons, and housings and exterior parts for home appliances and AV devices such as personal computers, mobile phones, and mobile devices.
Claims
1. A molding sheet with a protective film, comprising at least four layers laminated in this order: a layer (A layer) containing a polycarbonate-based resin; a layer (B layer) containing an acrylic-based resin; a layer (C layer) formed from an uncured product of an acrylate-based active energy ray-curable resin composition (composition C); and a protective film layer (D layer) containing a polycarbonate-based resin, wherein the glass transition temperatures (Tg) of the A layer and the D layer are 100°C or higher and 145°C or lower, and the absolute value of the glass transition temperature difference between the A layer and the D layer is 20°C or lower.
2. The thermoforming sheet with protective film according to claim 1, wherein the A layer and the D layer contain a polyester-based thermoplastic elastomer, and the polyester-based thermoplastic elastomer is composed of a hard segment composed of a polybutylene terephthalate unit and a soft segment composed of a polyester unit having an aromatic dicarboxylic acid and an aliphatic dicarboxylic acid as a dicarboxylic acid component and a diol having 5 to 15 carbon atoms as a diol component.
3. 3. The thermoforming sheet with a protective film according to claim 2, wherein the layers A and D contain 1 to 20 parts by weight of a polyester thermoplastic elastomer per 100 parts by weight of a polycarbonate resin.
4. 4. The thermoforming sheet with a protective film according to claim 1, wherein the C layer and the D layer are in direct contact with each other without any other layer therebetween.
5. The thermoforming sheet with protective films according to any one of claims 1 to 4, wherein the total thickness of the forming sheet with protective films is in the range of 0.05 mm or more and 3 mm or less.
6. 6. A decorative sheet with a protective film, comprising the thermoforming sheet with a protective film according to claim 1, and a decorative layer formed on the side of layer A opposite to the side of layers B, C and D.
7. A method for producing a molded body, comprising the steps of: forming the thermoforming sheet with a protective film according to any one of claims 1 to 5 or the decorative sheet with a protective film according to claim 6 into the shape of a mold cavity in advance; placing the sheet in the mold; and producing a molded body by integrating the sheet with the protective film and the decorative sheet with the protective film simultaneously with molding of a resin material; and then performing post-exposure to active energy rays, followed by peeling off the D layer.
8. A method for producing a molded body, comprising attaching the thermoforming sheet with a protective film according to any one of claims 1 to 5 or the decorative sheet with a protective film according to claim 6 to the cavity side of a mold by vacuum pressure, producing a molded body by integrating the sheet with the protective film and the decorative sheet with the protective film simultaneously with molding of a resin material, and then peeling off the D layer after performing post-exposure with active energy rays.
Citation Information
Patent Citations
Laminate hard coat film for molding, method for manufacturing the same, and method for manufacturing resin molding
JP2012210755A
Protective film-fitted resin laminate
JP2014180807A
Decorative polycarbonate film and molded article formed from the same
JP2020066206A
Decorative laminate member, and manufacturing method of decorative molded body
JP2020090084A